Downregulation of snoRNA SNORA52 and Its Clinical Significance in Hepatocellular Carcinoma. (7th June 2021) - Ding, Yuan; Sun, Zhongquan; Zhang, Sitong; Li, Yanjie; Han, Xin; Xu, Qianhui; Zhou, Liuzhi; Xu, Hao; Bai, Yang; Xu, Chang; Ding, Hao; Ge, Yao; et al.
Abstract : Hepatocellular carcinoma (HCC) is one of the most common and aggressive tumors in the world while the accuracy of the present tests for detecting HCC is poor. A novel diagnostic and prognostic biomarker for HCC is urgently needed. Overwhelming evidence has demonstrated the regulatory roles of small nucleolar RNA (snoRNA) in carcinogenesis. This study is aimed at analyzing the expression of a snoRNA, SNORA52, in HCC and exploring the correlation between its expression and various clinical characteristics of HCC patients. By using quantitative real-time PCR, we found that SNORA52 was downregulated in HCC cell lines (P < 0.05 ) and HCC tissues (P < 0.001 ). Correlation analysis showed that the expression of SNORA52 was obviously associated with tumor size (P = 0.011 ), lesion number (P = 0.007 ), capsular invasion (P = 0.011 ), tumor differentiation degree (P = 0.046 ), and TNM stage (P = 0.004 ). The disease-free survival (DFS) and overall survival (OS) analysis showed that patients with lower SNORA52 expression had a worse prognosis (P < 0.001 ). Univariate and multivariate Cox regression analysis showed that SNORA52 expression was a completely independent prognostic factor to predict DFS (P = 0.009 ) and OS (P = 0.012 ) of HCC patients. Overall, our findings showed SNORA52 expression levels were downregulated in HCC tissues and correlated with multiple clinical variables, and SNORA52 was an independent prognostic factor for HCC patients, which suggested that SNORA52 could function as a potential diagnostic and prognostic biomarker for HCC patients.